Poly[(mu(3)-4-carboxypyridine-3-carboxylato-kappa N-3:O-3:O-4)(triphenylphosphine-kappa P)silver(I)] - Sadeghi, O.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title 1:1 silver(I) 4-carboxypyridine-3-carboxylate adduct with triphenylphosphine, [Ag(C7H4NO4)(C18H15P)](n), the carboxylate anion bridges the phosphine-coordinated Ag atoms through its N and O atoms, generating a coordination polymer forming layers in the bc plane. The Ag atom exists in a distorted tetrahedral geometry. The H atom of the carboxylate is midway between two O atoms of the two carboxyl groups, thus forming a strong intramolecular hydrogen bond.